An Analysis on Household waste Management during Covid-19 Pandemic Era (Study at Suzuki Residents, North Minahasa) - Ika Saputri Wulandari; Soemarno Soemarno; Koderi Koderi (Indonesian Journal of Environment and Sustainable Development, 2021)
The purposes of this research were, (1) to analyze the characteristics of household waste arising during the Covid-19 Pandemic era, and (2) to describe the knowledge, perceptions and residents’ behavior in managing their waste during the Covid-19 Pandemic era. The method used in this research was quantitative method in which Suzuki Residence, Watutumou III Village, Kalawat District, City of North Minahasa, North Sulawesi Province, was used as research site. The results of the research found that the characteristics of household waste that obtained were 20.34 kg of total waste in seven days of measurement; the waste consisted of 49% plastic waste, 22% organic waste, 13% textile waste, 13% paper waste and 0.09% glass waste. The Residents' Perception of Home Waste Management tends to view the Recycle principle or recycling as the most efficient principle to solve the waste problem. The Residents' behavior in Home Waste Management were often littering and burning rubbish in the home environment. That it takes a comprehensive and sustainable socialization of waste management to the community, and is also followed by providing incentives and disincentives to people who want to reduce and or manage waste generated from household activities in the residence environment. Keywords: Management, Household Waste, Covid-19 Pandemic